Empreendedorismo feminino ou trabalho por conta própria? Um estudo sobre trabalhadoras na cidade de São Carlos/SP - Acquaro, Juliane (2018)
In the context of recent transformations in work, self-employment and small businesses have been viewed as alternatives to the traditional labour relations, composing a framework of new occupational arrangements and giving strength to the discourse of entrepreneurship and self-employment. Women, in part because of their common representation as more flexible, therefore more suited to the new demands of production, have conquered new spaces in the labor market, considered entrepreneurs in potencial. Issues related to maternity and domestic care are pointed out as factors that encourage women to engage in less regulated working positions, which make it possible to reconcile e multiple working shifts, favoring their participation in self-employment forms. To what extent the discourse of entrepreneurship re-signifies autonomous work activities and how this discourse is incorporated by the women who are in those activities that were analyzed in this research. The increase in the number of women in the entrepreneurial category in recent years, as well as the growth of movements that trigger the idea of ​​female entrepreneurship, are indications of a tendency to enhance flexible work and self-employment.This research aims to analyze the ways in which this insertion occurs, under what working conditions it is performed and how it is perceived by the women involved. The research was developed through a inquiry of digital content that addresses the category of female entrepreneurship, as well as field work in entrepreneurship events focused on women and interviews with entrepreneurs / self-employed women in the city of São Carlos-SP.